1998
DOI: 10.1073/pnas.95.4.1933
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-insensitive tobacco lacks nonhost resistance against soil-borne fungi

Abstract: Enhanced ethylene production is an early response of plants to pathogen attack and has been associated with both resistance and susceptibility to disease. Tobacco plants were transformed with the mutant etr1-1 gene from Arabidopsis, conferring dominant ethylene insensitivity. Besides lacking known ethylene responses, these transformants (Tetr) did not slow growth when contacting neighboring plants, hardly expressed defense-related basic pathogenesisrelated proteins, and developed spontaneous stem browning. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
196
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(216 citation statements)
references
References 33 publications
12
196
0
4
Order By: Relevance
“…We found similar results in an independent ethylene-insensitive transgenic line of tobacco (28% lower A max in line Tetr-20 [Knoester et al, 1998]; data not shown). Because Rubisco protein content was lower in the ethyleneinsensitive genotype (Table I), their lower A max is likely to be the result of a decrease in carboxylation capacity; Table I.…”
Section: Photosynthesis Of Vegetative Plantssupporting
confidence: 74%
See 1 more Smart Citation
“…We found similar results in an independent ethylene-insensitive transgenic line of tobacco (28% lower A max in line Tetr-20 [Knoester et al, 1998]; data not shown). Because Rubisco protein content was lower in the ethyleneinsensitive genotype (Table I), their lower A max is likely to be the result of a decrease in carboxylation capacity; Table I.…”
Section: Photosynthesis Of Vegetative Plantssupporting
confidence: 74%
“…Seeds of tobacco (Nicotiana tabacum 'Samsun NN') and transgenic lines expressing the mutant allele etr1-1 from Arabidopsis (Arabidopsis thaliana; Knoester et al, 1998) were provided by Professor L.C. van Loon (Utrecht University).…”
Section: Seedling Experimentsmentioning
confidence: 99%
“…Depending on the type of invader encountered, the plant appears to be capable of switching on the appropriate pathway or combination of pathways. The plant signalling molecules salicylic acid, jasmonic acid and ethylene play an important role in this signalling network: blocking the response to either of these signals can render plants more susceptible to pathogens and even insects 6, [49][50][51][52] . Resistance conferred by the salicylic acid-dependent pathway might be directed more against certain types of pathogens, whereas resistance conferred by salicylic acid-independent pathways might operate more effectively against other types of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the response to either of these signal molecules renders plants more susceptible to pathogens [17,22,43,46,55] and even insects [29]. Both JA and ethylene co-ordinate the activation of a large set of defense responses, and when applied exogenously can induce resistance themselves [4,6,39].…”
Section: Introductionmentioning
confidence: 99%